Feedback control of electrode offset voltage during functional electrical stimulation - Chu, Jun-Uk; Song, Kang-Il; Shon, Ahnsei; Han, Sungmin; Lee, Soo Hyun; Kang, Ji Yoon; Hwang, Dosik; Suh, Jun-Kyo Francis; Choi, Kuiwon; Youn, Inchan (ELSEVIER SCIENCE BV, 2013)
Control of the electrode offset voltage is an important issue related to the processes of functional electrical stimulation because excess charge accumulation over time damages both the tissue and the electrodes. This paper proposes a new feedback control scheme to regulate the electrode offset voltage to a predetermined reference value. The electrode offset voltage was continuously monitored using a sample-and-hold (S/H) circuit during stimulation and non-stimulation periods. The stimulation current was subsequently adjusted using a proportional-integral (PI) controller to minimise the error between the reference value and the electrode offset voltage. During the stimulation period, the electrode offset voltage was maintained through the S/H circuit, and the PI controller did not affect the amplitude of the stimulation current. In contrast, during the non-stimulation period, the electrode offset voltage was sampled through the S/H circuit and rapidly regulated through the PI controller. The experimental results obtained using a nerve cuff electrode showed that the electrode offset voltage was successfully controlled in terms of the performance specifications, such as the steady- and transient-state responses and the constraint of the controller output. Therefore, the proposed control scheme can potentially be used in various nerve stimulation devices and applications requiring control of the electrode offset voltage. (c) 2013 Elsevier B.V. All rights reserved.
Keywords: DEEP BRAIN-STIMULATION; NEURAL STIMULATION; IMPLANTS; SYSTEMS; DRIVER; NERVE; CHIP